TEMPEH JUICE AS POTENTIAL HEALTH SUPPORT CULINARY TOURISM - I Gusti Ayu Ari Agung (Institut Pariwisata dan Bisnis Internasional, 2016)
Tourism is part of the backbone the supports a country’s economic life. According to that fact, Indonesia should have a special concern by building a strong branding for it’s tourism. Tempeh juice culinary is one choice that has big potential to work out, because Indonesian’s most type tourists, they will always have a need to fill the stomach. The goal of the promotion is to increase the number of Indonesia’s foreign visitors, by giving impression and belief that tempeh juice as potential health has a unique, interesting, and cool sensation. Tempe is a traditional Indonesian food that are older than 1000 years. Tempeh is actually only be fermented in the area with warm temperatures such as in Indonesia. Promotion tempeh juice should be done consistently and continuously. The government is expected to be more creative in promoting tempeh juice health culinary, with the manufacture of various culinary travel guide books tempeh juice for health, in order to reach an increasing number of foreign tourists.